The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neurobiolaging.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

The association of mid-to late-life systemic inflammation with white matter structure in older adults: The Atherosclerosis Risk in Communities Study

Abstract: We examined whether the pattern of middle- to late-life systemic inflammation was associated with white matter structural abnormalities in older adults. 1,532 participants (age=76.5; SD=5.4) underwent 3T brain MRI to quantify white matter hyperintensity (WMH) volume and whole-brain WM microstructural integrity (fractional anisotropy, mean diffusivity). High-sensitivity C-reactive protein (CRP), a marker of systemic inflammation, was measured at three visits (21 and 14 years before, and concurrent with, neuroim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…Therefore, myostatin might directly decrease both lean mass and cognitive function, resulting in an association between them that might be stronger in men than women. Previous studies of chronic inflammation showed that it is associated with loss in lean mass and decline in white matter integrity 37–39 . Further studies are needed to understand the underlying mechanisms for the association of lean mass and dementia risk.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, myostatin might directly decrease both lean mass and cognitive function, resulting in an association between them that might be stronger in men than women. Previous studies of chronic inflammation showed that it is associated with loss in lean mass and decline in white matter integrity 37–39 . Further studies are needed to understand the underlying mechanisms for the association of lean mass and dementia risk.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, behavioral risk factors, such as smoking and diet, are also related to WM microstructural integrity (Gons et al, 2011; Launer et al, 2015; Gu et al, 2016). Finally, serum measures of systemic inflammation have also been associated with lower FA and greater MD, suggesting a potential inflammatory mechanism for microstructural integrity loss (Walker et al, 2017, 2018).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
“…Such dysregulation of the immune system has been linked to slowed processing speed both in aging and primary autoimmune conditions (Eckert, 2011;Heringa et al, 2014;Hughes et al, 2011;Shucard et al, 2007), and our finding that it may be both detectable and predictive of faster declines in processing speed supports a potential upstream role of the immune system in cognitive aging. Commensurate with these findings, a recent study demonstrated that higher concentrations of a systemic inflammatory marker (C-reactive protein) in middle-tolate age was significantly associated with cerebral white matter injury 14-years later (Walker et al, 2018). These converging findings support the predictive validity of peripherally-based cytokine markers and the immune system as an important target to promote future brain health states.…”
Section: Discussionmentioning
confidence: 64%